2017
DOI: 10.1080/17429145.2017.1373870
|View full text |Cite
|
Sign up to set email alerts
|

Central role of salicylic acid in resistance of safflower (Carthamus tinctoriusL.) against salinity

Abstract: The effects of salicylic acid (SA) on growth parameters and enzyme activities were investigated in saltstressed safflower (Carthamus tinctorius L.). Twenty-five days after sowing, seedlings were treated with NaCl (0, 100, and 200 mM) and SA (1 mM), and were harvested at 21 days after treatments. Results showed that some growth parameters decreased under salinity, while malondialdehyde (MDA) and hydrogen peroxide (H 2 O 2) content, phenolic compounds, and some enzyme activities increased. SA application increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 69 publications
(76 reference statements)
5
13
0
Order By: Relevance
“…In this experiment, growth parameters were inhibited under NaCl concentrations. Reduction of plant growth under salinity have been previously reported by other researchers [6,10,28]. Exogenous application of PEN prevented, to some extent, the negative effects of stress, especially in 200mM NaCl treated plants, and allowed increased plant growth (Table 1).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In this experiment, growth parameters were inhibited under NaCl concentrations. Reduction of plant growth under salinity have been previously reported by other researchers [6,10,28]. Exogenous application of PEN prevented, to some extent, the negative effects of stress, especially in 200mM NaCl treated plants, and allowed increased plant growth (Table 1).…”
Section: Discussionsupporting
confidence: 72%
“…However, its productivity decreases as the salinity level increases [5]. Under saline conditions, plants have adopted mechanisms to protect themselves by some strategies such as the accumulation of compatible solutes, the production of reactive oxygen species, and accumulation of important secondary metabolites [6]. The accumulation of compatible solutes such as proline and carbohydrate, which is in cytosole, is considered as a basic strategy for the protection of plants in response to stress conditions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the combined application of SA (0.005 mM) and/or Ca 2+ (0.5 mM) increased the phenolic and flavonoid content as well as the total antioxidant scavenging activity, which would help to alleviate the adverse effects of salinity stress on plant growth. Increase in growth and total soluble phenolic and flavonoid content due to SA application (50 and 250 μM) have also been reported in Matricaria chamomilla (Kovacik et al 2009), safflower (Carthamus tinctorius L.) (Shaki et al 2017), and Oueslati olive plants (Olea europaea L.) (Methenni et al 2018). In addition, increases have also been shown in wheat for the combined application of SA and Ca 2+ under saline conditions (Yucel and Heybet 2016).…”
Section: Discussionmentioning
confidence: 76%
“…Our previous work indicated that growth parameters which were followed by measuring fresh and dry weight of safflower plants were remarkably inhibited under different NaCl concentrations. However, the application of SA improved the negative effect of salinity by increasing plant growth especially in 200 mM NaCl-treated plants (Shaki et al 2017). In the current study, some biochemical and molecular parameters were investigated to better understand the effects of exogenous application of SA on safflower plants in saline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous works indicated that SA minimizes the negative effects of salt stress by improving growth parameters, accumulation of compatible solutes, and increasing antioxidant activity, and therefore, could be used for partial amelioration of salt stress in safflower (Shaki et al 2017(Shaki et al , 2018. To the best of our knowledge, there is no information available so far about the effect of SA on ions homeostasis, hormonal cross-talk and fatty acids compositions in salt-treated safflower plants.…”
Section: Introductionmentioning
confidence: 99%